INFLUENCE OF DISINFECTION, GROWTH MEDIUM AND PHYTOHORMONES IN THE IN VITRO MORPHOGENIC DEVELOPMENT OF GERMOPLASM OF Guazuma crinita Mart - GONZALES-ALVARADO, Antony Cristhian (2022)
The objective of this study was to determine the influence of disinfection processes, culture medium and phytohormones on the in vitro morphogenic development of explants obtained from biological seed of the species Guazuma crinita Mart (Bolaina), which was carried out in the tissue culture and meristems laboratory of the National University of Ucayali. The seeds were disinfected with 2% sodium hypochlorite for 0, 5, 10, 15 and 20 minutes (T1, T2, T3, T4, T5). To promote germination, culture media and combinations of Phytogel, Phytogel + Sucrose, Phytogel + Sucrose + Murashige and Skoog (MS) and Phytogel + Sucrose + ½ MS (M1, M2, M3, M4) were used; and for morphogenesis, five homogenized auxin and cytokinin concentration treatments were applied (AC1, AC2, AC3, AC4, AC5). From the study it was obtained that T5 (disinfection with 2% sodium hypochlorite with exposure of 20 minutes) had a 95% survival rate; while in germination, the M1 medium (Phytogel) presented the highest with 72.55%; Finally, in morphogenesis, it was determined that the best treatment for inducing callus formation was AC4 (Kin 12 ppm + AIB 12 ppm), for root primordia the best treatment was AC5 (Kin 4 ppm + AIB 12 ppm) and the same number of shoots was achieved with all the combinations of phytohormones used.